Information strategy design and practices - Mohapatra, Sanjay (Springer US, 2012)
Information Strategy Design and Practices illustrates approaches for designing and implementing information strategy. While it gives details of different theoretical concepts related to information strategy, it also provides live examples from different corporations as to how project goals can be achieved through effective information strategy. The book also illustrates 'people focused' frameworks that can be used for designing and implementing IS. It also demonstrates different approaches that would be of interest to practitioners.  The book has power point presentations for instructors which can be obtained from Springer.com.